The Importance of Legality of Businesses for Small and Medium Micro Businesses - Kusmanto, Heri; Warjio (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Business legality is a standard that must be fulfilled by business actors. Micro small and medium enterprises (MSMEs) entrepreneurs are required to fulfill these requirements in order to compete in the free market era. The demand is a problem because not a few business actors do not have business legality. Various obstacles were obtained such as the absence of funds to manage legality, the difficulty of correspondence, lack of knowledge and so on. In this paper, we will present the results of community service that have been carried out, namely the importance of business legality for MSMEs. The purpose of this service is to foster sensitivity (awareness) and build a framework of thinking on the importance of business legality for MSMEs in order to compete in the free market.